STUDY FISHING GROUND IN PLTA KOTO PANJANG RESERVOIR PULAU GADANGVILLAGE, XIII KOTO KAMPAR DISTRICT, PROVINCE OF RIAU - Charles Alison; Alit Hindri Yani; Polaris Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This study was conducted in juli2018 inPLTA Koto PanjangReserviorPulauGadang village, XIII Koto Kampar district, Province of Riau. Purpose of this study was to obtain data on environmental parameters become the benchmark fishing grounds and fishing activity there.Environmental parameters measured are temperature, current speed, brightness, depth, acidity (pH) and dissolved oxygen. After doing this research is that the condition of the PLTA Koto Panjang Reservoirvillage PulauGadangstill quite good and still support for life of organisms that were in it and deserves to fishing activities in these waters. Keyword : Fishing ground, environmental Parameters, PLTA Koto Panjang reservoir